2008
DOI: 10.1021/jp805678v
|View full text |Cite
|
Sign up to set email alerts
|

Population Inversion of a NAHS Mixture Adsorbed into a Cylindrical Pore

Abstract: A cylindrical nanopore immersed in a non-additive hard sphere binary fluid is studied by means of integral equation theories and Monte Carlo simulations. It is found that at low and intermediate values of the bulk total number density the more concentrated bulk species is preferentially absorbed by the pore, as expected. However, further increments of the bulk number density lead to an abrupt population inversion in the confined fluid and an entropy driven prewetting transition at the outside wall of the pore.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…The simplest one is the mixture of nonadditive hard spheres [24] in which the cross diameter is σ ij = 1/2(σ i + σ j )(1 + δ). Previous studies [9,13,14] have shown that when the pore is in equilibrium with a mixture in which one species is in minority (say x 2 = 0.02 for a non additivity parameter δ = 0.2 ) a population inversion occurs in the pore when the total bulk density is varied. This occurs here for ρ b between 0.55 and 0.56 for a pure non-additive HS mixture and between 0.54 and 0.55 for the hard-sphere dipole mixture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simplest one is the mixture of nonadditive hard spheres [24] in which the cross diameter is σ ij = 1/2(σ i + σ j )(1 + δ). Previous studies [9,13,14] have shown that when the pore is in equilibrium with a mixture in which one species is in minority (say x 2 = 0.02 for a non additivity parameter δ = 0.2 ) a population inversion occurs in the pore when the total bulk density is varied. This occurs here for ρ b between 0.55 and 0.56 for a pure non-additive HS mixture and between 0.54 and 0.55 for the hard-sphere dipole mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies considered the role of the pressure in one-component fluids (eg. [8]), or the total density and the mole fractions [9,13,14] in bulk mixtures but without field. As shown below, the combination of both will play here a crucial role.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This modified bridge density functional approach can be extended to the nonadditive hard-sphere mixtures adsorbed into pores in our previous work. 26,27 It would also be interesting to apply the present approximation for studying the exotic phase behavior occurring in model penetrable spheres such as the clustering transitions and the re-entrant melting phenomena. In addition to structural properties observed in this work, we are currently developing molecular dynamics simulation codes for studying the time-dependent transport properties of penetrable spheres with ultrasoft repulsive interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, σ p s0 corresponds to the AO limit (ideal polymers) and σ p N 0 to a particular non-additive hard sphere binary mixture. The phase separation of the NASH model was also studied for symmetric binary mixtures with different composition (σ a = σ b and Δ N 0) under confinement [53] leading to the so called population inversion effect [54] (clearly related to the capillarity condensation/evaporation phenomenon). It consists on that, under certain conditions, the more concentrated bulk species turns the less concentrated species inside the pore [55,56].…”
Section: Colloid-polymer Mixtures Under Confinementmentioning
confidence: 99%